“Oi, gente, cheguei para mais um picolé de limão”: a manutenção da contação de história no podcast Não Inviabilize - Pereira, Talysson Barbosa da Silveira (2025)
Drawing from the relationship between literature and other media, and addressing the issue of narrative in the expanded field, this dissertation aims to understand how storytelling is still present in our daily lives, even during a time of apparent decline. We can confirm this by observing the number of listeners, followers, and subscribers of the Não Inviabilize podcast, created by Déia Freitas, a Black woman from the ABC Paulista region, a psychologist by training, and an animal rights activist. The Não Inviabilize podcast has 15 segments (quadros), in which stories of different genres are told. To do this, we start with Benjamin's idea of experience (2020), which reports that in a society traumatized by the effects of war and capitalism, people have sought shallow experiences, unable to extract lessons from those moments. We continue our readings with the text "The Storyteller" (Benjamin, 2020), an essay in which we understand how narrating our experiences contributes to connecting us with other members of our community, as determined by Agamben (2005). For a story to resonate with the listener—that is, for it to be relevant to the spectator and create memories of that moment—the storyteller needs to be concerned with their performance, as Zumthor (2012) points out; thus, the presence of the body, conceived as the voice in the context of this research, is essential for establishing communication between the storyteller and the listener/spectator. Furthermore, we see that the practice of storytelling can occur through the radio. This medium arrived in Brazil at the beginning of the 20th century and went through several moments of decline but still maintains its market relevance, expanding onto the internet (Kischinhevsky, 2012; 2014). Finally, we observe that the act of storytelling is manifested in the Não Inviabilize podcast and keeps this tradition alive through oral performance by sharing lived experiences.